2015
DOI: 10.1371/journal.pone.0137725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fecal Microbiota in Children with Autism Spectrum Disorders and Neurotypical Siblings in the Simons Simplex Collection

Abstract: In order to assess potential associations between autism spectrum disorder (ASD) phenotype, functional GI disorders and fecal microbiota, we recruited simplex families, which had only a single ASD proband and neurotypical (NT) siblings, through the Simons Simplex Community at the Interactive Autism Network (SSC@IAN). Fecal samples and metadata related to functional GI disorders and diet were collected from ASD probands and NT siblings of ASD probands (age 7–14). Functional gastrointestinal disorders (FGID) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(206 citation statements)
references
References 64 publications
8
192
2
4
Order By: Relevance
“…Nonetheless, even when genome-sequencing methods were comparable, opposing microbiota profiles of the three major phyla (Firmicutes, Bacteroidetes, and Proteobacteria) were found in patients with ASD as compared to controls [58,59], or no difference was found at all [60]. Finegold et al [59] observed increased ratios of Bacteroidetes and Proteobacteria, but decreased ratios of Firmicutes in ASD patients, while Williams et al [58] also found increased ratios of Proteobacteria, they observed increased ratios of Firmicutes and decreased ratios of Bacteroidetes as opposed to Finegold et al [59].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 90%
“…Nonetheless, even when genome-sequencing methods were comparable, opposing microbiota profiles of the three major phyla (Firmicutes, Bacteroidetes, and Proteobacteria) were found in patients with ASD as compared to controls [58,59], or no difference was found at all [60]. Finegold et al [59] observed increased ratios of Bacteroidetes and Proteobacteria, but decreased ratios of Firmicutes in ASD patients, while Williams et al [58] also found increased ratios of Proteobacteria, they observed increased ratios of Firmicutes and decreased ratios of Bacteroidetes as opposed to Finegold et al [59].…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 90%
“…However, a subsequent study involving a larger population of autistic children reported the opposite result (i.e., a significant increase in Prevotella spp. [65]). In conclusion, the scientific literature is far from a final and unambiguous understanding of the role of a specific taxon in host health; plausibly, the same bacterial taxa of the gut microbiota may exert opposite effects on the host (health preserving versus health threatening), depending on physiological background.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance varied between 2 and 7% of total bacteria in the ileum and cecum. However, in another study no significant difference in the microbial composition, including the abundance of Sutterella , was observed between the autistic pediatric subjects with or without functional GI disorders compared to their siblings (Son et al, 2015). Thus, the results concerning the association of Sutterella spp.…”
Section: Introductionmentioning
confidence: 89%